1982
DOI: 10.1099/0022-1317-58-1-73
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-Cell Interactions Early After Infection: In vitro Characteristics and Tumourigenicity of Adenovirus Type 2-transformed Rat Liver Epithelial Cells

Abstract: SUMMARYCloned rat liver epithelial cells (clone C3) were semi-permissive for adenovirus type 2 (Ad-2) and non-permissive for adenovirus type 12 (Ad-12). Ad-2-infected C3 cells were shown to produce hexon and fibre protein, but at an m.o.i, of 20 a maximum virus yield of only 2.4 p.Lu. per cell was obtained. Forty-eight h after infection with Ad-12 'early' virus proteins (major species 8K and 60K), but no 'late' proteins (virus structural proteins) could be identified.Of six Ad-2-transformed epithelial lines is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1984
1984
1999
1999

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Immunoprecipitation was carried out on the supernatants by the procedure of Paraskeva et al (1982) except that protein G-agarose (Sigma) was used to bind antibody/antigen complexes, rather than protein A. Immunoprecipitations were carried out using XPH9 tissue culture supernatant (150 ml) for cells containing Ad12E1B54K protein or the fusion proteins or 2A6 (150 ml) for cells containing Ad2/5E1B58K protein. Immunoprecipitated proteins were subjected to SDS ± PAGE and were Western blotted using CM1 antibody against p53.…”
Section: Western Blotting and Immunoprecipitationmentioning
confidence: 99%
“…Immunoprecipitation was carried out on the supernatants by the procedure of Paraskeva et al (1982) except that protein G-agarose (Sigma) was used to bind antibody/antigen complexes, rather than protein A. Immunoprecipitations were carried out using XPH9 tissue culture supernatant (150 ml) for cells containing Ad12E1B54K protein or the fusion proteins or 2A6 (150 ml) for cells containing Ad2/5E1B58K protein. Immunoprecipitated proteins were subjected to SDS ± PAGE and were Western blotted using CM1 antibody against p53.…”
Section: Western Blotting and Immunoprecipitationmentioning
confidence: 99%
“…No comparable d After washing the cells were homogenised in 5 ml of buffered 10% sucrose and fractionated into nuclear, membrane and cytosolic fractions by differential centrifugation. The nuclear and membrane fractions were resuspended in the immunoprecipitation extraction buffer (0.5 ml) used by Paraskeva et al [17]. The cytosolic fraction was diluted 1: 1 with the same buffer.…”
Section: Effect Of Tunicamycin On [3h]paimitate Elb 18"kda Protein Wimentioning
confidence: 99%
“…In the light of the results which showed that lipid is bound to various transforming proteins [5,6] we have investigated whether any of the tumour antigens of Ad 12 are subject to a similar post-translational modification particularly as at least some of the 18-kDa protein has been shown to be membranebound [13]. [17] using specific Ad 12 rat tumour bearer sera (reactive only to Ela 41-and Elb 18-and 52-kDa proteins). Immunoprecipitates were dissolved in 9 M urea, 50 mM Tris-HCl (pH 7.5), 1% ,0-mercaptoethanol, 1% SDS (25 ~1) and run on 13% polyacrylamide gels in the presence of 0.1% SDS and 0.1 M Tris, 0.1 M Bicine (pH 8.3).…”
Section: Introductionmentioning
confidence: 99%
“…Immunoprecipitation was performed under`stringent' and mild' conditions.`Stringent' conditions were essentially as described by Paraskeva et al (1982) using bu ers containing 0.825 M NaCl and 1% NP40. Immunoprecipitation under`mild' conditions was carried out in the presence of 0.02% NP40, 5 mM ATP 10% glycerol and isotonic NaCl (Mason et al, 1998).…”
Section: Immunoprecipitation Polyacrylamide Gel Electrophoresis and mentioning
confidence: 99%